A Design and performance analysis of a telemetry system for remote monitoring of turbidity of water during the COVID-19 pandemic - Hasanah, Lilik; Hakim, Wahyu Luqmanul; Aminudin, Ahmad; Sahari, Siti Kudnie; Mulyanti, Budi (Universitas Pendidikan Indonesia, 2020)
A turbidity telemetry system for COVID-19 pandemic situations using nRF24L01+transceiver and SEN0189 water turbidity sensor-based microcontroller has been successfulyÂ developed.. The method used to characterize the sensor is by comparing sensor output voltages with the value of water turbidity. Turbid water used was created by adding distilled water with a concentration of sediment obtained from the filtered sediment with less than 60 Î¼m in diameter. Data transmission performance for various transmit power was done by calculating the error percentages by comparing the number of messages sent by transmitter and received by receiver. The transmit power settings were 0, -6, -12, and 18 dBm and variations in the distance of data transmission from 10 to 80 m. The test results show that the water turbidity sensor has a good measurement range in measuring turbidity of water from 1.873 to 3500 NTU. Higher concentrations of sediment and turbidity of the water made the sensor output voltage decrease. There was a decrease in output voltage in the value, namely -0.0006 in turbidity sensor sensitivity. The results also show an increase in error percentages as the distance of data transmission increases, while the bigger the transmit power is used for data transmission, the smaller the percentage of errors occurs.